Application of synopsys' taurus TCAD in developing CMOS fabrication process modules - Uda Hashim; Chin Seng Fatt; S. Sakrani (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://ijneam.unimap.edu.my/